The virtues of generosity and its antagonisms in Islam (Journal of Human Sciences, 2018)
The research explains the purpose of the act of generosity in the life of humanity, in some respects; from the Islamic religion, philosophical and human thought the ancient times to the present day. There have been a number of theoretical and practical contributions to the values ??of generosity and related meanings. It is one of the virtues that does not change according to time and place, but the scope of differences and the divergence of views, ideas and philosophies on this subject come in the ends of the act of generosity. The research problem is based on: What is the motive of doing or not doing generosity in life? Statement of the effect of generosity on the researcher is using the historical method and the deductive approach to derive the principles and general provisions of the texts studied. Among the results, the researcher used the historical method and the deductive approach to prepare a frame of reference in the educational and vocational preparation among those working in education. That means generosity is not linked to money and wealth, but sacrifices time, effort, science, permissibility, forgiveness, dream and pardon, when ability, and all that result from the protection of the souls of the evils of scab and vinegar and distension. That also includes other factors that strengthen ties of relevance, friendship, compassion, family and community members.